Mechano-chemical manipulation of Sn chains on Si(1 0 0) by NC-AFM. (30th December 2016) - Sweetman, A; Lekkas, I; Moriarty, P
Abstract: We investigate the atomic structure of Sn dimer chains grown on the Si(1 0 0) surface using non-contact atomic force microscopy (NC-AFM) at cryogenic temperatures. We find that similar to the native Si(1 0 0) dimer structure, the ground state of the Sn dimer structure is buckled at low temperature. At 5 K we show that the buckling state of the Sn dimers may be controllably, and reversibly, manipulated with atomic precision by close approach of the tip, without modification of the underlying substrate buckling structure. At intermediate cryogenic temperatures we observe changes in the configuration of the dimer chains in the region where the tip-sample interaction is very weak, suggesting that the energy barrier to transit between configurations is sufficiently small to be surmounted at 78 K.